Insurgent : One choice can destroy you - Roth, Veronica (New York, New York : HarperCollins Publishers, 2012)
As war surges in the factions of dystopian Chicago all around her, Tris attempts to save those she loves and herself while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love.